Networking and knowledge creation: Social capital and collaborative innovation in responding to the COVID-19 crisis - Khaled Saleh Al Omoush; Samuel Ribeiro-Navarrete; Carlos Lassala; Marinko éSkare (Journal of Innovation & Knowledge (JIK), 2022)
This study empirically explores the role of social capital in creating collaborative innovation and collective intelligence and maintaining organizational sustainability in the unprecedented COVID-19 crisis. Data were collected from a sample of 289 managers, directors and heads of departments of top 50 manufacturing firms in Jordan and analyzed using Smart-PLS-SEM. The results indicate that social capital significantly impacts collaborative innovation, collective intelligence and organization sustainability during the COVID-19 crisis. They also reveal that collective intelligence significantly impacts collaborative innovation and organization sustainability. This study enriches the literature on social capital, collaborative innovation and collective intelligence. It elucidates the role of such dynamic capabilities in maintaining both organizational sustainability and the chance of recovery from unprecedented crises.
Keywords: 650; Collaborative innovation; Collective intelligence; COVID-19; Organizational sustainability; Social capital